THE IMPACT OF DIGITAL LEARNING TECHNOLOGY ON THE QUALITY OF EDUCATION IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Nadya Putri Fitriani; Albertus Erico Jerry Krisna Nugroho; Ike Fitri Samsiyah; Auliya Rizqi Fitriyani; Sugiyanto; Aldora Kusbiarsi (SOSIOEDUKASI, 2025)
Advances in digital technology have had a major impact on education systems around the world, including in Indonesia. The implementation of various innovations such as e-learning, Learning Management Systems (LMS), artificial intelligence (AI), and virtual reality (VR/AR) technology has increased access to and enriched the learning process. However, challenges such as infrastructure limitations, low digital competence among educators, and lack of policy support remain obstacles to achieving quality education in the digital age. This study aims to comprehensively describe the influence of digital learning technology on the quality of education in Indonesia. The method used is a Systematic Literature Review (SLR) based on the PRISMA protocol. The results of the analysis reveal four main themes: (1) the effectiveness of digital-based learning in increasing motivation and learning achievement, (2) equitable access and the challenges of the digital divide, (3) educator readiness and digital capabilities, and (4) policies, infrastructure, and institutional support in driving educational transformation. These findings confirm that the success of digital learning implementation is not only determined by technology, but also by collaboration between educators, educational institutions, and government policies.